Penyuluhan Tentang Manfaat Sari Kacang Kedelai Terhadap Penurunan Tekanan Darah Pada Ibu hamil di Puskesmass Bontomarannu Kabupaten Gowa - Nurjannah Supardi (Pusat Riset dan Inovasi Nasional, 2023)
Hypertension in pregnancy is the presence of blood pressure of 140/90mmHg or more after 20 weeks of gestation in a woman who was previously normotensive, or an increase in systolic pressure of 30mmHg and/or diastolic pressure of 15mmHg above normal values. Various studies have been developed to provide better hypertension therapy. One of the potential sources of medicine is medicinal plants. Indonesia is a country that is very rich in natural resources and is very possible to cultivate. One of the reasons for using drugs from natural ingredients is their good effectiveness, relatively inexpensive, expected fewer side effects and easier for the body to accept because they are natural ingredients. Many of the plants around us are believed by the community to be used to lower blood pressure, for example soybean extract. It is hoped that after this counseling, pregnant women will know how to prevent hypertension during pregnancy.